The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11999-011-1800-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Wear of Cross-linked UHMWPE Using Magnesia-stabilized Zirconia Femoral Heads in a Hip Simulator

Abstract: Background To reduce wear, the ideal bearing surface in joint arthroplasty should be smooth and hydrophilic. Ceramics generally offer better wettability than metals and can be polished to a smoother finish. However, clinical studies have found no reduction in liner wear when using yttria-stabilized zirconia (Y-TZP) instead of cobalt chromium alloy (CoCr) femoral heads. Question/purposes We (1) determined whether a hard, diamond-like carbon (DLC) coating would enhance the wettability of CoCr and magnesia-stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
(74 reference statements)
0
3
0
1
Order By: Relevance
“…The first generation is called inert ceramics, which aimed to substitute natural bone. For example, zirconia [49][50][51][52], titanium [53][54][55] and alumina [56][57][58] are primarily used in fabrication of femoral heads to substitute the damaged bones [59]. Although these ceramics are biocompatible, the living body usually reacts against the implants because they are foreign, and these implants themselves are likely to never transform into bone.…”
Section: Evolution Of Bioceramics In Hard Tissue Engineeringmentioning
confidence: 99%
“…The first generation is called inert ceramics, which aimed to substitute natural bone. For example, zirconia [49][50][51][52], titanium [53][54][55] and alumina [56][57][58] are primarily used in fabrication of femoral heads to substitute the damaged bones [59]. Although these ceramics are biocompatible, the living body usually reacts against the implants because they are foreign, and these implants themselves are likely to never transform into bone.…”
Section: Evolution Of Bioceramics In Hard Tissue Engineeringmentioning
confidence: 99%
“…Though such coatings were able to improve the wear resistance of CoCrMo head in abrasion against UHMWPE, the wear damage of UHMWPE was not reduced, as reported in [16]. On the other hand, Roy et al [17] reported better performance of zirconia femoral head than CoCr femoral heads in bringing a lower wear rate of the UHMWPE counterpart. Li et al [18] reported zirconia-graphene composite coating prepared by plasma spraying, which showed reduced wear rate in dry sliding wear test against alumina.…”
Section: Introductionmentioning
confidence: 92%
“…Застосовуються конструкції з цементним типом фіксації переважно у хворих з ознаками остеопорозу, їх не рекомендується використовувати у пацієнтів молодого віку. Також при ревізійних операціях видалення цементу з невеликих кісток пов'язано з певними технічними труднощами [15,16].…”
Section: вступunclassified